IS THE AUDIT PROCEDURE DETERMINING THE AMOUNT OF DETERMINING THE AUDIT FEE? - Fachruddin, Wan; Pribadi, Angelia (Accounting and Business Journal, 2020)
This study aims to test audit experience, work pressure on the amount of audit fee determination based on the regulation of the Indonesian Public Accountants Association (IAPI) management regulation number 2 of 2016. A total of 112 questionnaires were distributed to auditors in the city of Medan, but only 69 questionnaires were processed. some respondents did not fill out the questionnaire completely. Tests conducted in this study use multiple regression to prove the effect of work experience and time pressure on audit fees. The results of this study indicate that partially work experience has no significant effect on audit fees. The time pressure partially has a significant effect on audit fees.